Mobility and Chain Value in a Nahua Town in the Northern Highlands of Puebla, Mexico - Eugenia D'Aubeterre Buznego; Leticia Rivermar Pérez (Íconos)
In this article we document the complex class experience of rural surplus populations that oscillate between periods of restricted mobility because of their relationships of dependence and moments of free circulation in the process of being absorbed by capital interests. The backdrop of this analysis is a classical ethnography of a Nahua speaking town in the Northern Highlands of Puebla, in the center of Mexico, which took place in the 1960s. We focus on the various ethnographic sites where flows of value were set off far away from producers, with the objective of making women and young people visible as economic subjects given that their work tends to be obscured by the census categories of “housewives” or “students”